AN ISLAMIC ECONOMIC LAW REVIEW OF THE QURBAN JOINT SAVINGS PRACTICE IN THE DARUT TAKWA TAKLIM ASSEMBLY - imalah141220, imalah141220 (Universitas Muhammadiyah Surabaya, 2025)
The focus of the problem in this study: 1) How is the Analysis of the Implementation of the Sacrificial Joint Savings in the Taklim Assembly Darut Takwa Village, B.Oro Konang District? 2) Is the Implementation of Sacrificial Joint Savings in the Darut Takwa Taklim Assembly of B.Oro Village, Konang District, in accordance with the HES Perspective? This research uses qualitative research methods. Data collection techniques using interviews, observations, and documentation studies. Data analysis using condensation, data presentation, and conclusion drawing. The results of this study 1) Implementation of the Sacrificial Joint Savings at the Darut Takwa Women's Assembly uses three processes. The first is the savings process, the second is the joint venture process, and the third is the process of representing the purchase of sacrificial animals. 2) Implementation of Sacrificial Savings in Majelis Taklim Darut Takwa, B.Oro Village, Konang District. The activity succeeded in having a positive impact on the taklim assembly participants and the community around the taklim assembly. The sacrificial savings activity succeeded in fostering interest in sacrificing the mothers of the taklim assembly and the surrounding community. 3) Implementation of Kurban Joint Savings in Majelis Taklim Darut Takwa, B.Oro Village, Konang Subdistrict, has been in accordance with the Sharia Economic Law Perspective. First, in accordance with the Fatwa DSN MUI. NO: 02/2000 about savings. Second, in accordance with Book 2 of the Complication of Sharia Economic Law, CHAPTER VII Articles 187-194 concerning Syirkah Milk. Third, in accordance with Fatwa DSN MUI. NO: 10/2000 about Wakalah.